A Chance to be kinder?: The Role of peer acceptance and rejection in the development of prosocial behavior in adolescence - Chávez, Daniela (fi=Turun yliopisto|en=University of Turku|, 2024)
Prosocial behavior, defined as voluntary actions intended to benefit others (e.g., helping, caring, sharing), has been both positively and negatively associated with peer status—namely, the extent to which individuals are liked (i.e., accepted) or disliked (i.e., rejected) by their peers. While much of the existing research has concentrated on children and young adults, often operationalizing peer status as the difference between acceptance ("liked most") and rejection ("liked least"), there remains a gap in understanding how peer acceptance and rejection influence the development of prosocial behavior during adolescence. The primary goals of this dissertation are to investigate longitudinally: (1) whether peer acceptance and rejection serve as precursors to or consequences of adolescents' prosocial behaviors; (2) how stable sociometric status profiles, based on levels of acceptance and rejection, can explain subsequent changes in adolescents' prosocial and aggressive behaviors; and (3) the extent to which adolescents adopt the prosocial behaviors of their (highly) liked classmates. To address these goals, three empirical studies were conducted using data from the ProCiviCo project in Chile. Study I investigated the longitudinal and bidirectional associations between prosocial behavior and peer acceptance/rejection. Study II examined peer status profiles based on peer acceptance and rejection, their stability over a 6-month interval, and how the affiliation to a specific profile predicted changes in both prosocial and aggressive behavior at the beginning of the new academic year. Finally, Study III tested the "contagion" effect of prosocial behavior based on liking preferences and whether both highly and less liked peers are more influential and influenced, respectively. The findings of this dissertation offer novel insights into the role of peer status —specifically acceptance/likeability and rejection/dislikeability— during adolescence and its impact on the development of prosocial behavior. These insights are derived from a longitudinal analysis across three-time points, employing three distinct methodological approaches: variable-oriented, person-oriented, and network-oriented approaches.